A Study on Topography Versus Sediment Yield Under Simulated Rainfall - Yong, L.K.; Law, P.L.; Siti Noor Linda, Taib; Ngu, J.O.K.; Mah, Yau Seng; Law, S.L.G. (IOP Publishing, 2021)
This study investigates the effects of topography on the amount of sediment yield under simulated rainfall. The slope gradient and length would affect the runoff depth (V) and peak flow volume (Qp) and thus the amount of surface runoffs. In this study, the simulated 150mm/hour rainfall intensity was applied on triangular prism-shaped, cone-shaped and pyramid-shaped models for determination of the amount of respective sediment yields (tons/storm event). It was observed that the sediment yields of the triangular prism-, cone- and pyramid-shaped amounted to 0.144, 0.143 and 0.125 tons/storm event, respectively. The triangular prism-shaped topography has the highest sediment yield amount as it experiences highest runoff depth and highest surface runoff velocity at downslope. Based on the experimental outcomes, it was shown that MUSLE could over-estimate sediment yield as much as 3.6 times for areas characterized by hilly landscape.